The Impact of Depression, Anxiety, Stress and Self-Esteem on Body Image Comparison of Young Adults - Ishana (My University, 2023)
The current study aims to evaluate the impact of depression, anxiety, stress and self-esteem on the body image comparison of young adults. The sample comprised 201 young adults (144 females, 57 males) between 18-25 years of age group. The data was collected using The Body Comparison Scale, Rosenberg self-esteem Scale and the Depression, Anxiety and Stress Scale - 21 Items. The results were computed using the Statistical Package for the Social Sciences (SPSS) and Microsoft Excel. The findings revealed a significant negative relationship between self-esteem and body image comparison.
Keywords: Depression; Anxiety; Stress; Self-esteem and Body image comparison